2015
DOI: 10.1038/onc.2015.268
|View full text |Cite
|
Sign up to set email alerts
|

E3 ligase EDD1/UBR5 is utilized by the HPV E6 oncogene to destabilize tumor suppressor TIP60

Abstract: Tat-interacting protein of 60 kDa (TIP60) is an essential lysine acetyltransferase implicated in transcription, DNA damage response and apoptosis. TIP60 protein expression is reduced in cancers. In cervical cancers, human papillomavirus (HPV) E6 oncogene targets cellular p53, Bak and some of the PDZ domain-containing proteins for proteasome-mediated degradation through E6AP ligase. Recently, E6 oncogene from high-risk and low-risk categories was also shown to target TIP60. However, the molecular mechanisms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…The 26S proteasome is one of the major cellular complexes interacting with UBE3A (21)(22)(23)(24)(25)(26)(27)(28)(29). Although immunoprecipitation and MS cannot distinguish which specific protein subunit within the 26S proteasome directly binds UBE3A, PSMD4 was the only proteasomal subunit identified as a direct UBE3Abinding partner in a yeast two-hybrid screen we recently reported, suggesting that PSMD4 likely bridges the interaction of UBE3A with the 26S proteasome (24).…”
Section: The 26s Proteasome Binds To the N Terminus Of Ube3amentioning
confidence: 87%
See 1 more Smart Citation
“…The 26S proteasome is one of the major cellular complexes interacting with UBE3A (21)(22)(23)(24)(25)(26)(27)(28)(29). Although immunoprecipitation and MS cannot distinguish which specific protein subunit within the 26S proteasome directly binds UBE3A, PSMD4 was the only proteasomal subunit identified as a direct UBE3Abinding partner in a yeast two-hybrid screen we recently reported, suggesting that PSMD4 likely bridges the interaction of UBE3A with the 26S proteasome (24).…”
Section: The 26s Proteasome Binds To the N Terminus Of Ube3amentioning
confidence: 87%
“…Although the proteins of the lid complex are responsible for the recruitment of ubiquitylated proteins, the barrel and its intrinsic proteolytic activities mediate the breakdown of proteins (20). UBE3A associates with the proteasome (21)(22)(23)(24)(25)(26)(27)(28)(29). In that context, the UBE3A-interacting protein PMSD4 (also known as Rpn10/S5a) is part of the regulatory lid complex and known to bind to polyubiquitin chains of ubiquitylated proteins via its ubiquitin-interacting motif (UIM), resulting in their recruitment to the proteasome (30 -32).…”
mentioning
confidence: 99%
“…EDD was among the E3 ubiquitin ligases identified by MS analysis of GRWD1-interacting proteins (Tables S1 and S2). EDD belongs to the HECT family of E3 ubiquitin ligases (Rotin and Kumar, 2009) and regulates the stability of various proteins such as topoisomerase II β-binding protein 1 (TopBP1) and Tat-interactive protein 60 (TIP60) (Honda et al, 2002;Subbaiah et al, 2016). The interaction between EDD and GRWD1 was confirmed by co-IP and immunoblotting (Fig.…”
Section: Comprehensive Identification Of Grwd1-interacting Proteinsmentioning
confidence: 76%
“…Thus fluctuations of EDD protein levels might directly affect the viral life cycle, and influence the development of HPV-induced malignancies [94]. In addition, it has also been shown that the association of EDD with HR HPV E6 is important in destabilizing TIP60; a histone acetyltransferase tumor suppressor, thus ultimately contributing to the development of HPV-induced malignancies [95].…”
Section: E6 Oncoprotein and Ubiquitin Ligasesmentioning
confidence: 99%